Tablet Ekstrak Daun Spondias pinnata: Pengaruh Variasi Primojel® dan Maltodekstrin terhadap Karakteristik dan Stabilitas Fisik serta Aktivitas Antioksidan - Suena, Ni Made Dharma Shantini; Mayuni, Putri Diah Gita; Dewi, Ni Nyoman Ayu Pramesti; Mendra, Ni Nyoman Yudianti; Rahadi, I Wayan Surya; Wardani, I Gusti Agung Ayu Kusuma (Jurnal Ilmiah Medicamento, 2025)
Cemcem leaves (Spondias pinnata) are rich in phenolic and flavonoid compounds with antioxidant potential. However, their traditional beverage form lacks stability, necessitating tablet formulation to improve stability and dosing convenience. This study evaluated the effect of varying concentrations of maltodextrin (binder) and Primojel® (disintegrant) on the physical quality and antioxidant activity of cemcem leaf extract tablets. Prior to formulation, extraction temperature optimization was performed using ultrasonic-assisted maceration at 30°C and 45°C, each for 3 minutes per cycle over three cycles. Three tablet formulations were prepared using optimized extract with different maltodextrin–Primojel® ratios: F1 (3%-8%), F2 (6.5%-5%), and F3 (10%-2%). Granule evaluation included moisture content, flow rate, angle of repose, and compressibility index. Tablets were assessed on days 1, 14, and 28 under room temperature storage for organoleptic properties, weight and size uniformity, hardness, friability, and disintegration time. Data were analyzed using Repeated Measures ANOVA and the Friedman test at a 95% confidence level. Extraction at 30°C yielded superior antioxidant activity, with lower IC₅₀ values and higher total flavonoid content and was therefore selected for formulation. All granules met physical quality standards; however, among tablet parameters, only disintegration time complied with pharmacopeial requirements. Formula F3, containing the highest maltodextrin concentration (10%) and lowest Primojel® concentration (2%), demonstrated the best physical stability from day 1 to day 28 (p > 0.05) and the strongest antioxidant activity, with the lowest IC₅₀ value (23.88 µg/mL; AAI 1.68). These findings confirm a causal relationship between excipient concentration and tablet performance, supporting F3 as a promising prototype for antioxidant supplement development.